CyTOF analysis of immune characteristics in cSLE: belimumab treatment and refractory cases - Luo, Ying; Wang, Linlin; Xu, Yongbin; Chen, Qian; Lam, Ki Pui; Zhu, Xiaona; Su, Qiru; Luo, Shuli; Yang, Jun (Frontiers in Immunology, 2026)
IntroductionSystemic lupus erythematosus (SLE) is a chronic autoimmune disease affecting multiple organs. Some patients still develop severe refractory SLE despite conventional treatments. Belimumab, a biologic targeting B lymphocyte stimulator (BLyS), shows therapeutic promise in SLE, but its effects on pediatric patients remain unclear.MethodsThis study used CyTOF to analyze immunophenotypic changes before and after belimumab treatment and investigate immune features in refractory SLE.ResultsResults showed that belimumab treatment primarily reduced transitional and naïve B cells, and also decreased age-associated B cells (ABCs), a subset implicated in autoimmunity or chronic inflammation. Plasma cells and plasmablasts persisted in refractory cases. CD38 expression on B cells was elevated in severe disease and correlated with disease activity, while CD73 expression increased during recovery and inversely correlated with activity.DiscussionThese findings indicate that combining belimumab with conventional therapy induces significant immune modulation, particularly within B cells. Persistent plasma cells and plasmablasts may contribute to disease refractoriness. CD38 and the CD73-mediated adenosine pathway may provide insights for future research strategies in SLE.